A study on the customer awareness of benefit scheme offered by SOCSO (Case: batik industry in Kelantan) / Siti Mariam Jusoh - Jusoh, Siti Mariam (2011)
The research is focusing on the “Customer awareness of Benefit Scheme offered by SOCSO”. As a social security in Malaysia, SOCSO realize that customer awareness is very important to ensure that all working Malaysian citizens have knowledge about SOCSO’s benefit and services. The employees should know about schemes that provide by SOCSO. There are because they still not aware towards SOCSO and the benefit scheme offered by SOCSO. SOCSO is committed to create a caring society to the employees. The main objectives of this study are (1) to identify the level of customer awareness towards benefit scheme offered by SOCSO; (2) to identify the factor contributes more towards consumer awareness of benefit scheme offered by SOCSO, (3) to determine the way and strategies to increase the customer awareness of benefit scheme by SOCSO. The respondents of this study were customers including the employers and employees in several of Batik Company in Kota Bharu area. 100 questionnaires had been distributed among them. The researcher had used the cluster sampling as sampling technique and the simple random sampling in every of company that chose. The process of analyzing and interpreting data has been presented with tables using method as reliability test, frequency and descriptive analysis. The researcher also had come out with a few of recommendations. By implementing these recommendations, the researcher optimism that it will help the SOCSO to better upgrade its performance and their management for future use that can enhance the level of awareness towards their benefits scheme.